Assessing the Validity, Practicality, and Effectiveness of Thematic-Integrative Teaching in Elementary Educatio - Wati, Salma; Aqodiah, Aqodiah; Mappanyompa, Mappanyompa (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
Integrative Thematic Learning is an educational approach that integrates various competencies from different subjects into a specific theme. This theme is current, closely related to the students' world, and present in their daily lives. This study aims to measure the validity, practicality, and effectiveness of integrative thematic teaching materials in elementary schools over a decade. Using a quantitative meta-analysis method, data were obtained from various databases identified based on established inclusion and exclusion criteria. The results showed that the validity of integrative thematic teaching materials reached 81%, while their effectiveness was 86%, and practicality was 85%. These findings indicate that the teaching materials have a high capability to enhance student learning performance and support their use in everyday learning processes. These findings provide a strong foundation for the development and implementation of curriculum teaching materials at the elementary level, as well as improving the quality of teaching and learning outcomes. Therefore, this study makes an important contribution to policymakers, educators, and curriculum developers in efforts to improve the quality of elementary education.